PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA DINAS KESEHATAN KOTA YOGYAKARTA - Triyono, Triyono; Suparyadi, Suparyadi; Lukitaningsih, Ambar (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
This research aims to know the influence between leadership style and compensation towards the performance of Yogyakarta Health Department. It used sensus method. Surveillance officers are the population also sample in this research amount to 45 people. The instrument used questionaire with likert scale and analyse tool used double regresion with T test and F test through significance of 0.05. The result can be concluded that (1) there is a significant positive effect on the Performance Leadership Style of Surveillance office at the Health department Yogyakarta with significant t> t table (2.755> 1.679), the value of β of 0.333 (2) there is a significant positive effect on the Performance Compensation of Surveillance office at the Health department Yogyakarta. with significant t> t table (2.440> 1.679), the value of β of 0.300. (3) there is a significant effect positive leadership style and Compensation for Performance of Surveillance office at the Health department Yogyakarta with significant the F count> F table (15.671> 2.84), the value of R² 0.534. Keywords: Compensation, Leadership Style, Performance